Is manipulation under anaesthesia still a better option than intra articular steroid injection in primary frozen shoulder? - Veeraraghavan, Raghav Ravi; Varghese, Venatius; A. K., Sanjay; Vanchi, Pravin Kumar; Murugesan, Mohan Kumar (International Journal of Research in Orthopaedics, 2020)
Background: Frozen shoulder, also known as adhesive capsulitis, is a common cause of a painful shoulder with restricted motion. The best treatment of frozen shoulder is prevention (secondary frozen shoulder), but early intervention is paramount; a good understanding of the pathologic process by the patient and the physician also is important. The aim of study is comparison between closed manipulation under anaesthesia and intra articular steroid injection in primary periarthritis shoulder. Methods: 30 patients each with primary frozen shoulder who were treated either with closed manipulation under anaesthesia and intra articular steroid injection. The patient is reassessed after 2 weeks, 1 month, 3 month and 6 months using shoulder pain and disability index (SPADI) and visual analogue scales (VAS) to compare the groups. Results: The SPADI index found to be better with patients under went closed manipulation under anaesthesia than intra articular steroid injection in the first 2 weeks. Follow up shows 1st group shows better outcome than 2nd group at 1 month, but later on 3 months and 6 months shows comparable results. VAS score shows initial period of improvement in pain with steroid injection (2nd group). Final follow up shows better pain relief with manipulation under anaesthesia group. Conclusions: The immediate treatment outcome is better with patients with primary frozen shoulder underwent closed manipulation under anaesthesia although following months outcome shows almost equal effectiveness with steroid injection.